THE EFFECT OF STORY MAPPING STRATEGY ON GRADE VIII STUDENTS’ ACHIEVEMENT IN WRITING NARRATIVE TEXT - Aryadi Manuel Gultom; Isli Iriani Indiah Pane (Universitas Negeri Medan, 2017)
This research aims at investigating the effect of story mapping strategy on grade VIII students’ achievement in writing narrative text. It was conducted by using experimental research design. The Population of this research was the eighth (VIII) grade students of St. Thomas 1 Junior High School Medan. There were two classes as the sample. The first class (VIII-F) as the experimental group, while the second class (VIII-B) as the control group. The experimental group was taught by using story mapping strategy while control group was taught by using lecturing strategy. The instrument for collecting the data was writing test. The data were analyzed by using t-test formula. The analysis showed that the score of students in the experimental group by using story mapping strategy was higher than the score of students in the control group by using lecturing strategy, at the level of significance (α) 0.05 with the degree of freedom (df) 38, the t-observed was 2,818 while the t-table was 2,024. Therefore, the applying of story mapping strategy significantly affected the students’ achievement in writing narrative text.